EFFECT OF AGNIHOTRA FUMES ON AEROMICROFLORA - R. R. PACHORI,; N. S. KULKARNI,; P. S. SADAR,; N. N. MAHAJAN, (The Bioscan, 2013)
Respiratory infections are the major cause of mortality and morbidity among the World population. Hence, with the view to control, the chemical fumigation is used as an adjunct to environmental cleaning of hospital rooms and other critical areas. However, chemical fogging possesses lots of hazardous effect and causes serious illness and death. The centers for Disease control and prevention (CDC) does not recommend chemical fogging to reduce air borne infections in routine patient care area. In contrast, Biofumigation is an effective, safe, inexpensive and ecofriendly technique for air disinfection. Hence, Focusing, on an ancient knowledge for disinfection of air, present study with the Agnihotra fumes on aeromicroflora of laboratory was carried out. The hawana was carried by Samidha using Palasa (Butea monosperma), Pimpal (Ficus religiosa), Udumbara (Ficus racemosa), Shami (Prosopis spicigera), Darbha (Desmostachya bipinnata), Rui (Calotropis gigantean), Khair, (Acacia chundra) Aghada (Achyranthes aspera) and Durva (Cynodon dactylon). The study indicates the decrease in growth response of aeromicroflora. Percent reductions of microbial count were 43, 30.84 and 56.07% for Bacteria Fungi and Actinomycetes respectively. Study enlight the possible scientific utility of Agnihotra for air disinfection to control respiratory infection.